Balancing Duniawi And Ukhrawi: A Case Study Of Three Malaysian Women Muslimpreneurs Msmes - Nur Aliya Amalin Ramli; Ummi Salwa Ahmad Bustamam; Syadiyah Abdul Shukor; Norasikin Salikin (University Technology Malaysia, 2024)
Non-Indexed Publication